Simulation of the process of cryogenic freezing of coriander seeds - N. V. Sterekhova; Z. A. Meretukov; S. Y. Gonezhuk; R. G. Shishova (Новые технологии)
In the technology for extracting the required components from plant raw materials, in most cases, the grinding process is used as a preparatory operation before the main process, followed by the separation of the extracted material into target components.In most cases, as a result of such a process, we can talk about the effective extraction of only a single target component, while others inevitably lose their qualitative and quantitative indicators, which is due to the morphology of the plant raw material.One of the promising directions in the processes of destruction of plant material for further operations is selective disintegration. For this purpose optimal process conditions have been selected, such as heating, freezing and others. Raw materials obtained as a result of selective destruction can be effectively fractionated according to morphological and physicochemical characteristics, and only after that can be sent to subsequent operations with the greatest efficiency.Under modern conditions, the loss of essential oil in coriander associated with splitting the fruit reaches 23.4% of the oil weight in whole fruits. At the same time, the essential oil from split fruits is enriched with valuable components – linalool, geraniol, geranyl acetate and, in addition, contains less hydrocarbons and camphor. As shown in [1], oil from split fruits can be used to adjust the composition of batches of coriander essential oil in order to increase the content of linalool while simultaneously reducing the content of undesirable components – hydrocarbons and camphor, and can also be used primarily to isolate valuable components – linalool, geraniol. To reduce losses associated with splitting coriander fruits, it has been proposed to carry out mathematical modeling of the process of cryogenic freezing with subsequent grinding of the frozen mass, which will significantly reduce losses of essential oil. Considering that essential oils extracted from coriander show high antibacterial, antioxidant and antifungal activity [2], increasing the yield of high-quality coriander essential oil will allow its wider use in flavoring and food preservation, as well as for medicinal purposes, which is important and actual task.